The separation of the East Australian Current: A Lagrangian approach to potential vorticity and upstream control. Issue 1 (22nd January 2016) - Ypma, S. L.; van Sebille, E.; Kiss, A. E.; Spence, P.
Abstract: The East Australian Current (EAC) is the western boundary current flowing along the east coast of Australia separating from the coast at approximately 34°S. After the separation two main pathways can be distinguished, the eastward flowing Tasman Front and the extension of the EAC flowing southward. The area south of the separation latitude is eddy‐rich and the separation latitude of the EAC is variable. Little is known of the properties of the water masses that separate at the bifurcation of the EAC. This paper presents new insights from the Lagrangian perspective, where the water masses that veer east and those that continue south are tracked in an eddy‐permitting numerical model. The transport along the two pathways is computed, and a 1:3 ratio between transport in the EAC extension and transport in the Tasman Front is found. The results show that the "fate" of the particles is to first order already determined by the particle distribution within the EAC current upstream of the separation latitude, where 85% of the particles following the EAC extension originate from below 460 m and 90% of the particles following the Tasman Front originate from the top 460 m depth at 28°S. The separation and pathways are controlled by the structure of the isopycnals in this region. Analysis of anomalies in potential vorticity show that in the region where the two water masses overlap, the fate of the water depends on the presence of anticyclonic eddies that push isopycnals down and therefore enable particles to travel further south. Key Points: The East Australia Current separates at 34°S Controls on fate of water are investigated Depth of water is main control, with deep water flowing south